Análise do alongamento das carteiras dos fundos de previdência complementar aberta - Vianna Junior, Paulo Roberto Miller Fernandes (2015)
This study aims at analyzing the retirement funds fixed income portfolios’ duration, which are paradoxically short considering the long-term objectives inherent to retirement savings, and the effects of the existing incentives to persistence on the employer sponsored collective plans, such as the contribution from the sponsor and vesting clauses, on the portfolios’ duration. In order to overcome the difficulties in directly observing the analyzed funds portfolios’ durations, it is proposed a duration index built upon the Return Based Style Analysis developed by SHARPE (1992) using the principal components of the Anbima’s Constant Duration Indexes (IDkA) to evaluate the retirement funds monthly returns sensibility to the nominal and real interest rates curves. The obtained results do not show evidences that the funds exclusively linked to employer sponsored collective plans present longer durations than those linked to individual plans or notsponsored collective plans. On the other hand, funds classified as 'Target Date' stand out for presenting longer duration indexes when compared to funds classified as 'Fixed Income' or 'Balanced Portfolios' and show positive correlation with the target year of the fund. This suggest that policies aiming at treating the information set of the agent’s, both investors and portfolio managers, are able to modify the investments allocation. Information is sufficient to improve allocation.